Livremente: Clube de Leitura da Biblioteca da Fundação Educacional São Carlos (FESC) - Angelon, Elisabete Maria (2024)
Loneliness has been identified as a global epidemic and declared by the World Health Organisation as a factor that affects the mental health of people of all ages. Population aging is another factor of concern as most elderly people live alone. Several countries already implement public policies to alleviate the problem. The São Carlos Educational Foundation (FESC), located in the central region of the State of São Paulo, provides lifelong education and socialization activities for people. The majority of FESC students are elderly. Intergenerational dialogic practices are important in the processes of building knowledge and culture in contemporary times. Through consciously exercised information mediation, librarians can reveal their social protagonism and contribute to the formation of a more humane and fair society. The observation of the five dimensions that can be achieved in information mediation, which are: the dialogic dimension, the aesthetic dimension, the ethical dimension, the formative dimension and the political dimension, indicate the effectiveness of the activities of a more humanizing mediation, in line with the sociocultural context in which they take place. In the aesthetic dimension of information mediation, bibliotherapy operates, an action in which the subject can exercise recognition of themselves and others and experience the resignification of their emotions. Reading clubs are groups of people who come together to practice shared reading, they provide encouragement for reading, a sense of well-being for participants and relief from tension. This research aimed to highlight how the mediation of information exercised consciously can promote the socialization of people in the context of reading clubs. This research took a qualitative approach, the method used was a case study in “Livremente”, the FESC Library Reading Club, which is an intergenerational reading club. The techniques used were participant observation, application of a semi-structured questionnaire, collection of statements and photographs. The results indicate that exchange of experiences between people of different age groups in a reading club bring enriching experiences in educational, cultural and social processes. The information mediation activities developed in “Livremente” reached the dialogical, aesthetic, ethical and formative dimensions of information. In the perception of the aesthetic dimension of information, there were indications of bibliotherapy. It was concluded that reading clubs are a valuable tool for increasing the reading habit, expanding knowledge, development of critical thinking, improving self-esteem, emotional awareness, reframing experiences, self-knowledge, leisure, friendship bonds, and a sense of belonging. Librarians can exercise their social role by working in reading clubs to promote the appropriation of information, cultural appropriation and socialization of people.